Impact of Graded Passive Cycling on Hemodynamics, Cerebral Blood Flow, and Cardiac Function in Septic ICU Patients - Chen, Jennifer; Martin, Claudio; Ball, Ian M.; McIntyre, Christopher W.; Slessarev, Marat (Frontiers in Medicine, 2020)
Background: In-bed passive cycling is considered a safe and feasible early mobilization technique in intensive care unit (ICU) patients who are unable to exercise actively. However, the impact of varying intensity of passive cycling on perfusion and function of ischemia prone organs is unknown. In this study, we assessed the impact of a graded passive cycling protocol on hemodynamics, cerebral blood flow and cardiac function in a cohort of septic ICU patients. Methods: In consecutive patients presenting with sepsis, we measured global hemodynamic indices, middle cerebral artery velocity (MCAv), and cardiac function in response to a graded increase in passive cycling cadence. Using 5 min stages, we increased cadence from 5 to 55 RPM in increments of 10 RPM, preceded and followed by 5 min baseline and recovery periods at 0 RPM. The mean values obtained during the last 2 min of each stage were compared within and between subjects for all metrics using repeated measures ANOVA. Results: Ten septic patients (six males) completed the protocol. Across patients, there was a 5.2% reduction in MCAv from baseline at cycling cadences of 25-45 RPM, with a dose-dependent decrease of MCAv of >10% in four of the ten patients enrolled. There was a 16% increase in total peripheral resistance from baseline at peak cadence of 55 RPMs, and no changes in any other measured hemodynamic parameters. Patient responses to passive cycling varied between patients in terms of magnitude, direction of change, and the cycling cadence at which these changes occurred. Conclusions: In septic patients, graded passive cycling is associated with dose-dependent decreases in cerebral blood flow, increases in total peripheral resistance, and either improvement or worsening of left ventricular function. The magnitude and cadence threshold of these responses vary between patients. Future studies should establish whether these changes are associated with clinical outcomes including cognitive impairment, vasopressor use, and functional outcomes.